Simplify.7 square root of 3 end root minus 4 square root of 6 end root plus square root of 48 end root minus square root of 54

A) 11 square root of 6 end root minus 7 square root of 12
B) 11 square root of 3 end root minus 7 square root of 6
C) negative 3 square root of 9
D) 4 square root of 9

Respuesta :

7√3-4√6+√48-√54
√48=√(16*3)=4√3
√54=√(9*6)=3√6

7√3-4√6+4√3-3√6=
7√3+4√3-4√6-3√6=
11√5-7√6

B is answer
[tex]7\sqrt{3}-4\sqrt{6}+\sqrt{48}-\sqrt{54}=7\sqrt{3}-4\sqrt{6}+\sqrt{16\times3}-\sqrt{9\times6}\\=7\sqrt{3}-4\sqrt{6}+4\sqrt{3}-3\sqrt{6}=11\sqrt{3}-7\sqrt{6}[/tex]